2012
DOI: 10.4187/respcare.01093
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Care Practices and Requirements for Respiratory Therapists in Beijing Intensive Care Units

Abstract: ICU respiratory care equipment and the knowledge to use them are insufficient. Important differences exist in respiratory care practice, which is mostly provided by nurses and physicians. RTs have been gradually recognized and accepted by ICU staff, while professional training and education are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
2
14
0
1
Order By: Relevance
“…Because there are no respiratory therapists in Japan, nurses were responsible for a greater proportion of care of mechanically ventilated patients, 18 and the same may apply for practice in other countries. Li et al 19 reported that variable clinical practices in ICU respiratory care exist and are provided mostly by nurses and physicians because of the lack of respiratory therapists. Experience-based knowledge was indicated by nurses as one of the categories of their sources of knowledge in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are no respiratory therapists in Japan, nurses were responsible for a greater proportion of care of mechanically ventilated patients, 18 and the same may apply for practice in other countries. Li et al 19 reported that variable clinical practices in ICU respiratory care exist and are provided mostly by nurses and physicians because of the lack of respiratory therapists. Experience-based knowledge was indicated by nurses as one of the categories of their sources of knowledge in practice.…”
Section: Discussionmentioning
confidence: 99%
“…CP can be defined as the external application of a combination of forces to increase expiratory flow with the goal to optimize mucus transport . CP in general, and PSE and AC in particular, is used in human infants and adults for the removal of retained airway secretions . This variety of techniques are designed to help improve the patient's respiratory strength, control the sensations of dyspnea, and to help improve gas exchange .…”
Section: Discussionmentioning
confidence: 99%
“…It is considered especially helpful for patients with large amounts of secretions or ineffective cough . Physiotherapy is commonly implemented in human intensive care units . CP has been reported to reduce the duration of mechanical ventilation, length of hospitalization, incidence of ventilator‐associated pneumonia, and risk of mortality in human ICU patients .…”
Section: Introductionmentioning
confidence: 99%
“…14 It might be due to lack of trained multidisciplinary professionals, such as respiratory therapists, as shown in our previous study. 24 It is very important to identify the possibility of successful weaning in patients requiring PMV. Dermot Frengley et al 25 recently found that weaning success decreased with age, higher comorbidity burden, and more-severe illness, which was in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%